The Impact of Parental Financial Socialization on Student Financial Satisfaction through Digital Financial Management Behavior (Study on Payment Fintech Indonesia) - Adam Nurkholik (Journal of Innovative and Creativity, 2025)
A significant number of students utilize payment fintech, yet their financial satisfaction levels differ. By investigating the mediating function of students' digital financial management behavior, this study seeks to elucidate the relationship between parental financial socialization and students' financial satisfaction. This study distributed 410 questionnaires to Gen Z college students, and then the collected data was analyzed in the form of demographics of respondents and the PLS-SEM technique by using software SmartPLS 4. According to demographic data, the survey population is primarily made up of young women who rely heavily on their parents for housing and financial support while making do with a meager daily allowance. All the indicators used to describe construct variables in the outer model measurement were reliable and valid. Furthermore, the structural model's goodness-of-fit was strong and fit in the inner model assessment, all hypotheses had significantly positive effects, and the behavior variable for digital financial management served as a complementary mediator. The study's findings provide valuable insights into how parental financial socialization can significantly enhance students' financial behaviors and satisfaction, particularly in the context of emerging fintech solutions. It emphasizes the necessity for educational institutions to prioritize financial literacy initiatives that actively involve parents, ensuring students are equipped to manage their finances effectively in a digital economy. This study still has a narrow scope; to improve the findings' generalizability, future studies should broaden to encompass a variety of demographic groups and geographic contexts.